OPTIMIZING RESOURCES IN THE INTERCROPPING FARMING SYSTEM IN TABANAN REGENCY, BALI PROVINCE - Ni Putu Sukanteri; Putu Fajar Kartika Lestari; Ni Putu Anglila Amaral (Faculty of Animal and Agricultural Science, Diponegoro University, 2023)
Land as a location for farming is the main asset managed by farmers. Land area is directly proportional to farm production. the wider the land managed, the higher the production produced. In the intercropping farming system, it shows that the land is used for the production of several commodities such as cocoa, coconut, bananas and cattle, if the commodities cultivated do not experience significant disturbances. The aim of the research is to analyze the gross income of smallholder plantation farming in Angkah Village, to analyze the allocation of agricultural resources with a cacao-coconut-banana crop intercropping system and cattle in Angkah Village. The research was conducted in Angkah Village, Selemadeg Barat District, Tabanan Regency, on an intercropping farming system. Research on optimizing resource allocation uses a linear programming approach, which is a formal mathematical technique that selects combinations and activity levels, of all feasible activities to achieve the objective function without neglecting the availability of resources, and other specified constraints. The gross income earned by farmers in Angkah Village is an average of Rp. 45,728,824 per year. This income is obtained from the intercropping system of cocoa, coconut, bananas and cattle. Farming is carried out on an average land area of 0.53 ha for cocoa. 0.071 ha for coconut land, 0.061 for banana land and 0.014 ha for cattle. The optimal income is 69,800,035. The amount of agricultural resource allocation with an intercropping system of cacao-coconut-banana crops and cattle in Angkah Village is 1,042 HOK. Changes in commodity prices cause changes in commodity income in the intercropping system in Angkah Village.